DIGITAL MEDIA IMPLEMENTATION IN 21st CENTURY IPS LEARNING AT SD NEGERI 2 TANJUNG KUKUH OGAN KOMERING ULU TIMUR - Putri Gasa Nopa; Endie Riyoko; Kabib Sholeh (CV. Fahr Publishing, 2023)
Digital-based learning media is a medium used to create audio-visual media. Digital media is very suitable for use in social studies learning in the 21st century. In the 21st century students are expected to be able to master 21st century skills with the 4C concept of communication, collaboration, critical thinking and problem solving, creative and innovative. The objectives of this study are 1) Knowing the steps for implementing digital media in 21st century social studies learning, 2) implementing digital media in 21st century social studies learning, and 3) evaluating the implementation of digital media using SWOT analysis in 21st century social studies learning. The research method used is qualitative by using the results of data analysis in the form of qualitative descriptive. Data collection techniques using observation, interviews, questionnaires, and documentation. The results of the research can be seen in the SWOT analysis which shows that the advantages of implementing digital media in social studies learning really need to be applied in the 21st century. Weaknesses in this study can be seen when observing students' attitudes in social studies learning on local history material regarding the role of local figures in fighting for Indonesian independence. Most of the students are still a lot preoccupied with themselves so that the center of attention is not fully paying attention to the future. In addition, it is a challenge for students to be able to express opinions and be more active. Opportunities in this study indicate that digital media is effectively used in the 21st century as a learning medium. Keywords: Digital Media, IPS, 21st Century.